Fe3O4 Nanoparticles Enhanced Amorphous Ferric Silicate/Reduced Graphene Oxide for High‐Performance Lithium‐Ion Storage. Issue 28 (6th September 2022) - Li, Huan; Tang, Chunjuan; An, Xiuyun; Li, Jili; Min, Zhiyu; Wang, Fang; Liang, Chaoxi; Wang, Changqing; Han, Dongfeng; Liu, Jia
Abstract: Ferric silicate (FS) has been explored as a potential lithium ion batteries candidate for its environment benign, low cost, rich reserves, and high capacity. Despite these advantages, poor electronic conductivity and large volume variation obstruct its practical utilization. To improve its electrochemical performance, a unique hybrid structure with Fe3 O4 @ferric silicate nanosheets anchored on the reduced graphene oxide (FO@FS/RGO) is fabricated. The disordered amorphous nanosheet structure of FS not only shortens the transferred length for lithium ions but also facilities the Li + diffusion and can effectively keep the structure integrity. RGO substrate ameliorates the electronic conductivity and slackens the strain upon cycling. Fe3 O4 (FO) nanoparticles embedded in FS further boost the electronic conductivity and the lithium storage capability. The synergistic effects bestow the composite superior electrochemical properties. FO@FS/RGO shows high reversible capacity of 1113 mA h g −1 at 0.2 A g −1, an excellent rate performance of 681 mA h g −1 at 2 A g −1, and a splendid cycling stability with a capacity of 859 mA h g −1 at 1 A g −1 after 800 cycles. Abstract : To improve the electrochemical performance of ferric silicate, a unique hybrid structure with Fe3 O4 @ferric silicate nanosheets anchored on the reduced graphene oxide is fabricated. The composite shows high reversible capacity of 1113 mA h g −1 at 0.2 A g −1 and a splendid cycling stability with a capacity of 859 mA h g −1 at 1 A g −1 after 800 cycles.